2000
DOI: 10.1007/s000110050577
|View full text |Cite
|
Sign up to set email alerts
|

Participation of endogenous endothelins in delayed eosinophil and neutrophil recruitment in mouse pleurisy

Abstract: Endothelins, acting via ETA receptors, play a role in late eosinophil and neutrophil accumulation (24 h), but not in the acute (4 h) neutrophilic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
8
21
0
1
Order By: Relevance
“…5). These results support the previous finding of significant suppression by BQ-123 of the eosinophil accumulation in BALF in sensitized mice after antigen challenge [7,26,33]. Based on these findings, we speculate that ET-1(1-31) elicits eosinophil recruitment, probably through an ET A receptor, similar to the mechanism of action of ET-1.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…5). These results support the previous finding of significant suppression by BQ-123 of the eosinophil accumulation in BALF in sensitized mice after antigen challenge [7,26,33]. Based on these findings, we speculate that ET-1(1-31) elicits eosinophil recruitment, probably through an ET A receptor, similar to the mechanism of action of ET-1.…”
Section: Discussionsupporting
confidence: 81%
“…In this paper, we first reported that ET-1(1-31) and ET-1 stimulate the generation of eotaxin through a BQ-123-sensitive ET A or ET A -like receptor, resulting in the recruitment of eosinophils to the injected loci. Although it has been reported that the production of IL-5 evoked by an antigen is inhibited by BQ-123 [26], we demonstrated stimulatory effects of ET-1(1-31) and ET-1 on the production of IL-5 in non-immunized mice and their remarkable effects in IL-5 transgenic mice (Figs. 2 and 3).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[12][13][14] The present work provides evidence for several relevant mechanisms underlying this potential benefit. We propose that the beneficial role of ω-3 PUFA on SCD vascular dysfunction might be exerted: (i) directly through the reduction of ET-1 expression, which is involved in adaptive inflammation, expression of adhesion molecules such as VCAM-1, and neutrophil chemotaxis; 46 and (ii) indirectly through reduced inflammation and oxidative stress. Importantly, the ω-3 PUFA supplementation in our study is comparable to that achieved in recent human studies.…”
Section: Discussionmentioning
confidence: 99%
“…Está bem demonstrado que a injeção intratorácica de zimosan e carragenina induziu um intenso extravasamento protéico, bem como a migração de leucócitos, para a cavidade pleural de camundongos (HENRIQUES, et al 1990;SAMPAIO;ERA;HENRIQUES, 2000). , 1996).…”
Section: Atividade Farmacológicaunclassified